Medico-legal aspect of patient safety for online consultation and telemedicine: A Literature Review - Affrita, Tia Maya; Sujari Solichin; Widyana Beta Arthanti (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
Abstract COVID-19 is an infectious disease caused by SARS-CoV-2 and spread through droplet transmission which makes it easy to spreads fast, especially from human to human interaction. It means that doctor-patient interaction in healthcare settings also prone to be one of the transmission points. Telemedicine is used to decrease the transmission of COVID-19 in healthcare settings since health service will be done without a human on human contact during the process and replaced by online interaction instead. The changing between face to face examinations to the online examination will change the course of health services on how examination should be done and what kind of consideration to take when treating the patient. This raise a question on the legal aspect of safety and the quality issues of online examination. A literature review with the legal aspect of patient safety during online health care as the main focus. Based on the suggestion from the Indonesian Doctor Association, a review of standard operating procedures is needed for online health service. This new standard will be focusing on how to build a good clinical practice that maintains the aspect of patient safety of conventional practice while reducing the risk for COVID-19 transmission. A new standard operating procedure which patient safety and quality of service become a priority is needed so telemedicine can be developed to be used as an alternative in the COVID-19 pandemic era Keywords— COVID-19, telemedicine, patient safety, standard operational procedure, medico-legal